2022
DOI: 10.3389/fsoc.2022.763088
|View full text |Cite
|
Sign up to set email alerts
|

Women's Experience of Depressive Symptoms While Working From Home During the COVID-19 Pandemic: Evidence From an International Web Survey

Abstract: The COVID-19 pandemic led to significant changes in workplace practices as social distancing requirements meant that people were asked to work from home where possible to avoid unnecessary contact. Concerns have been raised about the effects of the pandemic on mental health and, in particular, the effects of social distancing on employed women's mental health. In this study, we explore the experiences of working women during the initial stages of the COVID-19 pandemic and explore the factors that may be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
0
12
1
Order By: Relevance
“…This understanding will help organizational strategists and managers develop work-based responses that may support greater gender equality. Interestingly, there were statistically significant wellbeing effects of commute time [54] and psychological distress in women [56], but not statistically significant in men. In this regard, while these studies offer a useful nomological map as to how women experience telework differently, they seem to lack the controls required to understand what differences are experienced based on gender individual differences as compared to environmental, cultural, and social differences that adversely effect people of diverse genders.…”
Section: Gender-based Differences (Sdg 5)mentioning
confidence: 85%
See 2 more Smart Citations
“…This understanding will help organizational strategists and managers develop work-based responses that may support greater gender equality. Interestingly, there were statistically significant wellbeing effects of commute time [54] and psychological distress in women [56], but not statistically significant in men. In this regard, while these studies offer a useful nomological map as to how women experience telework differently, they seem to lack the controls required to understand what differences are experienced based on gender individual differences as compared to environmental, cultural, and social differences that adversely effect people of diverse genders.…”
Section: Gender-based Differences (Sdg 5)mentioning
confidence: 85%
“…Likewise, emotional exhaustion was considered higher in women [53], but relaxation levels were also higher in women. A key area that requires greater clarity includes stress [39], depression symptoms [54,27], and loneliness [20]. This understanding will help organizational strategists and managers develop work-based responses that may support greater gender equality.…”
Section: Gender-based Differences (Sdg 5)mentioning
confidence: 99%
See 1 more Smart Citation
“…Dealing with the pandemic in such a situation, following strict policies and restrictions such as lockdowns and quarantine, could adversely affect people’s mental health [ 13 ]. A cross-sectional study conducted in five European countries (France, Italy, Poland, Sweden, and the UK) found that working from home due to COVID-19 to maintain social distance negatively influenced employed women’s mental health [ 14 ]. In Bangladesh, the first COVID-19 case was confirmed on 8 March 2020, and the government followed the lockdown policies to prevent rapid transmission among people from 26 March 2020—this had been extended several times up to the first quarter of 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2020) have also noted the dominance of depression, anxiety scores, and PTSD symptoms among women during the pandemic. Burn, et al, (2022), found that signs of depression were more prevalent among women working from home compared to travelling to a workplace. Salari et al (2020) provided evidence that vulnerability for depression, stress, and PTSD has surfaced more in women than in men.…”
Section: Introductionmentioning
confidence: 99%